“Performance analysis of solar thermal collectors: A comprehensive review” - Tejas V. Kadam; Shrawan Y. Pakhare; Akshay B. Godse (Measurement: Energy, 2025)
Solar thermal collectors (STCs) are central to the transition toward sustainable energy systems, enabling the conversion of solar radiation into useable heat for residential, commercial, and industrial applications. This review presents a critical analysis of the performance, classification, and recent advancements in STCs, including flat-plate collectors, evacuated tube collectors, concentrating systems, and hybrid photovoltaic/thermal configurations. Emphasis is placed on the evaluation of key performance metrics—thermal efficiency, optical properties, and fluid dynamics—under standardized protocols such as ASHRAE 93–2003 and ISO 9806. The review further explores state-of-the-art enhancements involving nanofluids, selective coatings, and phase change materials (PCMs), highlighting their effectiveness and integration challenges. Special attention is given to instrumentation techniques, measurement uncertainties, and real-time monitoring systems used in performance assessment. Finally, emerging research directions, including intelligent control strategies, hybridization, and climate-adaptive designs, are discussed to guide future development of more efficient, durable, and scalable solar thermal technologies.